A fundamentação constitucional da tutela penal da ordem econômica - Campana, Eduardo Luiz Michelan (2011)
This dissertation analyzes the constitutional economic order as a value source of Criminal Law. The research starts by analyzing the impact on the criminal systems of the different conceptions of State, checking on the features of Criminal Law in a Democratic and Social Rule-of-Law State. Analyzing constitutional criminal principles and values, constitutional theories on the criminal-juridical good, constitutional subpoenas, Economic Criminal Law and dispositions that establish the formal economic Constitution, allows for evaluation of the foundation present in the Federal Constitution of 1988 for criminal liability regarding proceedings that harm, or put in harm s ways the economic order. The supraindividual goods established by the Constitution form the social basis of the Rule-of-Law and require their enforcement and protection so as to perform social justice, including by punitive state interventions in new scopes, among which the economic order stands out. From the ruling content and meaning of the various constitutional provisions that it brings, which are in accordance with the Republic's foundations and objectives, it is particularly noticeable the relevance and axiological density of the Brazilian democratic state s economic order. The principles, foundations and objectives of the economic order reveal constitutional values of undisputable importance, a safe direction to attest its criminal value, supporting the investigation about the lack of legal protection, legitimizing the criminalization of procedures that result in social harm, besides authorizing a discussion about criminalization clauses. Constitutional foundation for legal protection of the economic order leads necessarily to the study of adequate instruments to face economic crimes, which requires an approach of Criminal Economic Law, a criminal right that involves danger or risk, resorting to open criminal types, blank criminal regulations and analogical interpretation, all of which are tools that, when adequately applied, seek to confer effectiveness to the punitive state s intervention for the protection of the economic order